2000
DOI: 10.1021/ja0014281
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Solvent Effect of Water in Radical Reaction:  Triethylborane-Induced Atom-Transfer Radical Cyclization in Water

Abstract: Triethylborane-induced atom-transfer radical cyclization of iodo acetals and iodoacetates in water is described. Radical cyclization of iodo acetal proceeded smoothly both in aqueous methanol and in water. Atom-transfer radical cyclization of allyl iodoacetate (3a) is much more efficient in water than in benzene or hexane. For instance, treatment of 3a with triethylborane in benzene or hexane at room temperature did not yield the desired lactone. In contrast, 3a cyclized much more smoothly in water and yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(117 citation statements)
references
References 48 publications
4
107
0
6
Order By: Relevance
“…[36][37][38][39][40][41] Waluk and co-workers found that hydrogen-bonded complexes with one or two water molecules will greatly decrease the energy barrier for a protontransfer reaction. DFT calculations also found that 7-azaindole clustered with four water molecules could explain the rate increase relative to the 7-azaindole monomer clustered with two and three water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38][39][40][41] Waluk and co-workers found that hydrogen-bonded complexes with one or two water molecules will greatly decrease the energy barrier for a protontransfer reaction. DFT calculations also found that 7-azaindole clustered with four water molecules could explain the rate increase relative to the 7-azaindole monomer clustered with two and three water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…However, a report last year indicated that triethylborane-induced atom transfer radical cyclization reactions proceeded much more effectively in water than in the traditional organic solvents. 16 In contrast to the relative lack of data in the organic literature, water has long been a popular solvent for carrying out freeradical polymerizations, 17,18 especially of fluorinated monomers. 19 Although most fluoropolymers are now made by dispersion, emulsion, or suspension polymerizations in aqueous media, there are still problems associated with this field that make studies of absolute rates of fluoroalkyl radicals in water of some importance.…”
Section: Discussionmentioning
confidence: 99%
“…14a) [36], iodoamides [37], α-iodonitriles [36], and simple alkyl iodides [38] to alkenes and alkynes have been reported. Interestingly, these reactions were also performed with success in aqueous media [13,39,40] demonstrating the ability of Et 3 B to act as initiator in water (Eq. 14b) [41].…”
Section: Iodine Atom Transfermentioning
confidence: 99%